Development and validation of a score to detect paroxysmal atrial fibrillation after stroke. (8th January 2019) - Uphaus, Timo; Weber-Krüger, Mark; Grond, Martin; Toenges, Gerrit; Jahn-Eimermacher, Antje; Jauss, Marek; Kirchhof, Paulus; Wachter, Rolf; Gröschel, Klaus
Abstract : Objective: Prolonged monitoring times (72 hours) are recommended to detect paroxysmal atrial fibrillation (pAF) after ischemic stroke but this is not yet clinical practice; therefore, an individual patient selection for prolonged ECG monitoring might increase the diagnostic yield of pAF in a resource-saving manner. Methods: We used individual patient data from 3 prospective studies (ntotal = 1, 556) performing prolonged Holter-ECG monitoring (at least 72 hours) and centralized data evaluation after TIA or stroke in patients with sinus rhythm. Based on the TRIPOD (Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis) guideline, a clinical score was developed on one cohort, internally validated by bootstrapping, and externally validated on 2 other studies. Results: pAF was detected in 77 of 1, 556 patients (4.9%) during 72 hours of Holter monitoring. After logistic regression analysis with variable selection, age and the qualifying stroke event (categorized as stroke severity with NIH Stroke Scale [NIHSS] score ⩽5 [odds ratio 2.4 vs TIA; 95% confidence interval 0.8–6.9, p = 0.112] or stroke with NIHSS score >5 [odds ratio 7.2 vs TIA; 95% confidence interval 2.4–21.8, p < 0.001]) were found to be predictive for the detection of pAF within 72 hours of Holter monitoring and included in the final score (Age: 0.76 points/year, Stroke Severity NIHSS ⩽5 = 9 points, NIHSS >5 = 21 points; to Find AF [AS5F]). The high-risk group defined by AS5F is characterized by a predicted risk between 5.2% and 40.8% for detection of pAF with a number needed to screen of 3 for the highest observed AS5F points within the study population. Regarding the low number of outcomes before generalization of AS5F, the results need replication. Conclusion: The AS5F score can select patients for prolonged ECG monitoring after ischemic stroke to detect pAF. Classification of evidence: This study provides Class I evidence that the AS5F score accurately identifies patients with ischemic stroke at a higher risk of pAF.